2017
DOI: 10.1111/plb.12624
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis, using RNA‐Seq of Lomandra longifolia roots infected with Phytophthora cinnamomi reveals the complexity of the resistance response

Abstract: The plant pathogen Phytophthora cinnamon the causal agent of disease in numerous species, is a major threat to natural vegetation and has economic impacts in agriculture. The pathogen principally invades the root system, which, in susceptible species, is rapidly colonised and functionally destroyed. Few species are resistant, however, where resistance is expressed the pathogen is restricted to small, localised lesions. The molecular mechanisms that underpin this response in resistant species are not well under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
(91 reference statements)
1
5
0
Order By: Relevance
“…Jasmonic acid is also an important signaling molecule in plant disease resistance responses. Many studies have shown that plants initiate JA−dependent responses upon exposure to necrotrophs (Mengiste, 2012;Qi et al, 2012;Pandey et al, 2016;Islam et al, 2018). In the present study, the content of JA in E+ and E− leaves was not affected by the biotrophic pathogen Erysiphales species but was increased by the necrotrophic pathogen C. lunata, which was consistent with the conclusions of previous research.…”
Section: Leaf Damagesupporting
confidence: 93%
“…Jasmonic acid is also an important signaling molecule in plant disease resistance responses. Many studies have shown that plants initiate JA−dependent responses upon exposure to necrotrophs (Mengiste, 2012;Qi et al, 2012;Pandey et al, 2016;Islam et al, 2018). In the present study, the content of JA in E+ and E− leaves was not affected by the biotrophic pathogen Erysiphales species but was increased by the necrotrophic pathogen C. lunata, which was consistent with the conclusions of previous research.…”
Section: Leaf Damagesupporting
confidence: 93%
“…The transcriptome has been widely used to study the defense response in plants and to identify specific genes that interact with pathogens. In Lomandra longifolia roots, callose synthase genes, MAPK 15, 2 PR genes, and 5 receptor-like protein genes were found to be significantly expressed when infected by Phytophthora cinnamomi 18 . In N. benthamiana leaves, expression of 13 b-1,3-glucanases from the PR-2 family, and 16 chitinases from the PR-3, PR-4, PR-8, and PR-11 families were induced following infection with P. parasitica 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Equally importantly, each seaweed extract was found to exert its effect through different subsets of genes. A number of studies explored plant transcriptomes following abiotic and biotic stress (see for example: Tommasini et al, 2008;Allardyce et al, 2013;GonñI et al, 2016;Islam et al, 2018;Jithesh et al, 2019), however, the present study is the first report of a comprehensive transcriptome analysis, following treatment of plants with seaweed extracts, root pathogen infection and analysis over multiple time points.…”
Section: Summary Of Transcriptional Changes Induced By Each Seaweed Ementioning
confidence: 99%